Sifat Kewirausahaan dan Prestasi Usaha Kecil dan Menengah Sumatera Barat (Suatu Kajian Empiris) - Herri, .; Irda, . (Jurnal Widya Manajemen & Akuntansi, 2005)
The main objective of this research was to test empirically the influence of entrepreneur's behaviors and business characteristics to the firms performance. The research tries to integrate internal and external factors in determining firms performance.